Renaissance war studies - Hale, J. R. (John Rigby), 1923-1999 (History series (Hambledon Press), 1983)
Beginning with the chapters on warfare in the first three volumes of the New Cambridge Modern History, Sir John Hale's writings on the subject present an original and rich assessment of war's place in Renaissance life and thought. The first section of this collection constitutes a major contribution to the study of Renaissance fortifications, their design, planning and execution, and their political as well as their military significance. The second deals with the recruitment and training of officers and men. In the third, contemporary reactions to war are analysed in a variety of social and i.